2009
DOI: 10.1177/1479164109346359
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle risk factors for atherosclerosis in adults with type 1 diabetes

Abstract: The objective of this study was to compare the amount of self-reported physical activity, alcohol and tobacco use in a large sample of adults with type 1 diabetes and non-diabetic subjects. A second aim is to test the hypothesis that these lifestyle risk factors are associated cross-sectionally with coronary artery calcification. In 2000-2002, the Coronary Artery Calcification in Type 1 Diabetes (CACTI) study applied validated questionnaires for smoking, alcohol and physical activity to 582 type 1 diabetes sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
1

Year Published

2010
2010
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 26 publications
1
29
1
Order By: Relevance
“…Of the eight studies that reported an association between physical activity and CVD there were five cross-sectional studies (Kriska AM et al 1991;Herbst A et al 2007;Valerio G et al 2007;Bishop et al 2009;Trigona B et al 2010) and three trials (Lehmann R et al 1997;Fuchsjäger-Mayrl G et al 2002;Seeger JPH et al 2011). No prospective cohort studies were found.…”
Section: Physical Activitymentioning
confidence: 99%
See 4 more Smart Citations
“…Of the eight studies that reported an association between physical activity and CVD there were five cross-sectional studies (Kriska AM et al 1991;Herbst A et al 2007;Valerio G et al 2007;Bishop et al 2009;Trigona B et al 2010) and three trials (Lehmann R et al 1997;Fuchsjäger-Mayrl G et al 2002;Seeger JPH et al 2011). No prospective cohort studies were found.…”
Section: Physical Activitymentioning
confidence: 99%
“…Impaired endothelial function is considered as an early sign of atherosclerosis, which is often the underlying cause of CVD. And finally, (Bishop et al 2009) a significant inverse association between physical activity and CAC, a marker of coronary artery atherosclerosis, was demonstrated. In conclusion all these studies found a beneficial effect of physical activity on cardiovascular risk factors.…”
Section: Physical Activitymentioning
confidence: 99%
See 3 more Smart Citations